1976
DOI: 10.2466/pr0.1976.38.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Note on Males' and Females' Preferences for Opposite-Sex Body Parts, Bust Sizes, and Bust-Revealing Clothing

Abstract: In Study 1, 55 young women responded that they preferred men with hairy chests and circumcised penises. The chest was the male body part reported to be most “sexually stimulating” to females. The busts were the female body part most “sexually stimulating” to males ( n = 34). In Study 2, men ( n = 35) preferred larger busts than women typically possess on the average, but the women ( n = 48) tended to overestimate the bust size most preferred by males. The ratings of bust-revealing clothing showed the males wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…A study of Chinese MSM found that 15% thought MC would improve the partner's sexual pleasure, while 4% thought it would decrease it, and 68% were unsure [96]. In sub-Saharan Africa, 69% (range 47-79%) of women preferred circumcision for their partners because of its perceived aesthetic value [101], consistent with credible studies in developed countries [170,171]. …”
Section: Discussionsupporting
confidence: 53%
“…A study of Chinese MSM found that 15% thought MC would improve the partner's sexual pleasure, while 4% thought it would decrease it, and 68% were unsure [96]. In sub-Saharan Africa, 69% (range 47-79%) of women preferred circumcision for their partners because of its perceived aesthetic value [101], consistent with credible studies in developed countries [170,171]. …”
Section: Discussionsupporting
confidence: 53%
“…Men rated more highly a female figure with breasts larger than the average size (Beck, Ward-Hull, & McLear, 1976). Wildman, Wildman, Brown, and Trice (1976) reported that the bust was the most sexually stimulating female body part for males, and men have a preference for female busts that are larger than what women possess on average. Research has also indicated that women's bust size influences men's behavior.…”
Section: Women's Physical Appearance and Men's Judgmentmentioning
confidence: 97%
“…In a survey of undergraduate women at Georgia College, Milledgeville, Georgia, on viewing color magazine photographs of men with “well-formed body parts,” 89% preferred the circumcised penis and 11% preferred the uncircumcised penis 16 …”
Section: Women’s Preference For Circumcised Menmentioning
confidence: 99%